Pengetahuan dan sikap siswa SMA Negeri 1 Kakas Kabupaten Minahasa mengenai kekerasan dalam rumah tangga - Putra, Racmad Pratama Suhardi; Siagian, Iyone E. T.; Palandeng, Henry M. F. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2017)
Domestic violence is one of the many female health problems occur in the Indonesia domestic violence according to the legislation of the Republic of Indonesia Number 23 2014 is every one's deeds are mainly women, which resulted in the incidence of misery or suffering physical, sexual, psychological, and or deprivation of liberty unlawfully within the household.. The number of cases of domestic violence recorded by the 2015 National Commission on Anti violence against women the National Commission of women mention that as much as 11,207 case in the realm of domestic violence, 60% or 6,725 case in the form of violence against the wife of 24% or 2,734 cases of violence in dating, and 8% or 930 cases of violence against girls. Physical abuse was ranked first with 38% percentage or 4,304 cases, followed by sexual violence 30% or 3,325 cases, violent psychic 23% or 2,607, and economy 9% or 971 cases. The purpose of this study was to obtain information about the overview of the knowledge and attitude of high school students in Kakas 1 about domestic violence. This research is descriptive research design. Sources respondents taken from all students in 1st High School Kakas, Minahasa.Keywords: student's knowledge, student's attitude, domestic violence